Precision Grinding of Hard and Brittle Materials - Venkatesh, Vellore Chelvaraj; Sudin, Izman; Sharif, Safian; Mon, Thet Thet; Konneh, Mohamed (Universiti Putra Malaysia Press, 2004)
Two novel techniques were used to study the formation of ductile mode streaks during diamond grinding (primary process) of germanium, silicon, and glass that aid the secondary process of polishing. In the first technique asph~ric surfaces were generated on Ge and Si at conventional speeds (5000 rpm). In the second technique high speed grinding (100,000 rpm) of plano surfaces on glass and Si surfaces was carried out Form accuracy, surface finish and ductile mode grinding streaks are discussed in this paper. It was found that resinoid diamond wheels gave more ductile streaks than metal-bonded wheels but better form accuracy was obtained with the latter. Transparent ground surfaces were obtained more easily with Pyrex rather than with BK 7 glass, thus necessitating very little time for polishing. Ductile streaks appeared in abundance on germanium rather than silicon. Both the novel grinding techniques were used on CNC machining centres.